Design and Research on Terminal Structure of 8.5 kV UHV Thyristor With Low Proportion - Chen ZHANG; Dong LIU; Maosen TANG; Zeyu WU; Zongyao ZHOU; Xinglai GE (机车电传动)
As an important device for energy conversion and transmission, high-power thyristors are widely used in fields such as high-voltage direct current transmission. With the increasing requirements of the power grid for the transmission power capacity,increasing the conduction capacity of the thyristor has attracted much attention. However, as the capacity increases, the conventional straight-line oblique angle modeling technology may reduce the effective conduction area of the cathode while ensuring that the angle is small enough. In order to solve this problem, a high-power thyristor with a low-occupancy terminal structure was studied. In this thyristor, a broken line shape was adopted to achieve a smaller angle on the terminal structure side to achieve the same electric field optimization as a line oblique angle. Meanwhile, the effective conduction area of the cathode could be ensured. Finally, a TCAD model of an 8.5kV thyristor device was established and analyzed by using the Silvaco platform to verify the feasibility of the proposed structure.